A Comparative Life Cycle Assessment (LCA) of Monopole Antenna and Microwave Oven for Water Heating - Shatha Al-Doori; Bassim Abbassi; Omar Ramahi (Computational Engineering and Physical Modeling)
Conducting a life cycle assessment (LCA) for technologies used for water heating is crucial for understanding their environmental impacts throughout their entire life cycles. This analysis facilitates the evaluation of resource consumption, energy usage, and emissions associated with each technology. Accordingly, a comparative LCA of a monopole antenna and microwave oven for water heating is presented in this research in order to identify the most environmentally sustainable alternative. Utilizing the SimaPro software, the results were assessed with TRACI 2.1 method for characterized and normalized data. The comparative LCA for both systems heating 1 L of water with electromagnetic radiation shows that the monopole antenna has a lower environmental impact than the microwave oven. In all environmental impact categories, the microwave oven's environmental impacts were found to be greater than 97.5% of a monopole antenna's. Using the monopole antenna can reduce GWP-related emissions by 36.37 g CO2 eq/L compared to the microwave oven. The results of this study demonstrate the monopole antenna's significant environmental advantages over the microwave oven in water heating applications. The monopole antenna exhibited consistently lower impacts across all assessed environmental categories, including global warming potential, smog, acidification, and eutrophication. These outcomes underscore the monopole antenna's potential as a sustainable alternative for water heating, with implications for reducing ecological footprints in everyday applications.